2015
DOI: 10.1007/s00436-015-4382-6
|View full text |Cite
|
Sign up to set email alerts
|

Pearsonema plica (Capillaria plica) infection and associated urinary bladder pathology in red foxes (Vulpes vulpes) from Bosnia and Herzegovina

Abstract: Pearsonema plica is a widely distributed nematode parasite that occurs in the urinary tract of various domestic and wild carnivores. The aim of this study was to investigate the occurrence and geographical distribution of P. plica and associated urinary bladder pathology in 112 red foxes (70 males, 42 females; 87 adults >1 year, 25 juveniles <1 year) from six different geographical regions in Bosnia and Herzegovina. The urinary bladders of the red foxes were subjected to gross examination and histopathology. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Lesions of the urinary bladder associated with P. plica infection previously observed in dogs (Senior et al, 1980) and in an arctic fox (Alopex lagopus) (Fernández-Aguilar et al, 2010) were characterized by predominant eosinophilic infl ammation along with infi ltration of lymphocytes or occasional plasma cells. Chronic follicular cystitis has been recently described in infected red foxes, but it has been considered a less common fi nding compared to the eosinophilic cystitis (Alić et al, 2015). Data from this study are the fi rst report of lesions associated with P. plica infection in the wolf.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Lesions of the urinary bladder associated with P. plica infection previously observed in dogs (Senior et al, 1980) and in an arctic fox (Alopex lagopus) (Fernández-Aguilar et al, 2010) were characterized by predominant eosinophilic infl ammation along with infi ltration of lymphocytes or occasional plasma cells. Chronic follicular cystitis has been recently described in infected red foxes, but it has been considered a less common fi nding compared to the eosinophilic cystitis (Alić et al, 2015). Data from this study are the fi rst report of lesions associated with P. plica infection in the wolf.…”
Section: Discussionmentioning
confidence: 57%
“…P. plica is considered to be of low pathogenic signifi cance and in most cases parasite establishes only asymptomatic infections (Fernández-Aguilar et al, 2010). However, in heavy parasite loads P. plica has been found to be responsible for urinary signs and lesions in both carnivore pets (Callegari et al, 2010;Rossi et al, 2011;Basso et al, 2013) and wild canids (Fernández-Aguilar et al, 2010;Bork-Mimm & Rinder, 2011;Alić et al, 2015). In wolves, P. plica infection has been previously reported in Belarus (Shimalov & Shimalov, 2000), Spain (Segovia et al, 2001) and Latvia (Bagrade et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, urinary capillariosis has often been regarded as having minor clinical and pathological significance, due to frequent subclinical presentations and limitations in its diagnosis (Otranto, 2015). However, in heavy parasite loads, P. plica may be responsible for severe lower urinary tract maladies, both in domestic (Rossi et al, 2011;Basso et al, 2014) and wild carnivores (Fernández-Aguilar et al, 2010;Bork-Mimm and Rinder, 2011;Alić et al, 2015). These urinary disorders generally include pollakiuria, dysuria and hematuria, may have chronic or recurrent clinical forms and do not improve after symptomatic or empirical antibiotic treatments (Senior et al, 1980;van Veen, 2002;Rossi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, especially in case of P. plica heavy parasite burdens, the infection has been accounted for urinary clinical signs and bladder lesions, both in domestic carnivores ( Senior et al, 1980 ; Callegari et al, 2010 ; Rossi et al, 2011 ) and in wild canids. Lesions associated with P. plica infection generally consist of eosinophilic or lymphocytic infiltration of urinary bladder, kidney and ureters in foxes ( Fernandez-Aguilar et al, 2010 ; Bork-Mimm and Rinder, 2011 ; Alić et al, 2015 ), while follicular chronic cystitis has been reported in wolves ( Mariacher et al, 2015 ). In the bear of the present case, only scattered hyperemic foci in the bladder mucosa and mild cystitis were observed.…”
Section: Resultsmentioning
confidence: 99%